High performance rechargeable aluminium ion batteries enabled by strategy of covalent organic frame material - Wei, Guokang; Qiao, Jia; Li, Xin; Dou, Aichun; Hu, Sijiang; Xie, Wei; Luo, Zhenhua; Yang, Jianhong (Elsevier, 2025)
Emerging rechargeable aluminium-ion batteries (RAIBs) are a sustainable option for the next generation of low-cost, high-safety and large-scale energy storage technologies. While the unsatisfying availability of traditional inorganic materials has limited the development of RAIBs, the advance of organic materials is expected to be a breakthrough towards high-performance cathode. However, the existing extensive research often focuses on the selection of appropriate organic monomers or stay in the tentative stage of preliminary polymerization. It is difficult to break through the inherent characteristics of the instability of small organic ones and the easy aggregation and accumulation of macromolecular polymers, which is no doubt ignoring the huge potential of organic compounds for structural design at the molecular level. In this connection, our study demonstrates a material design strategy that introduces active functional groups to small molecular monomers and polymerizes them into REDOX active covalent organic framework (COF) with multiple N-containing groups. Theoretical simulations and ex-situ analysis revealed the key function of C-N and C=N as active sites for reversible storage of AlCl2 + ions. In addition, the macro-ring frame brings enhanced structural stability and environmental tolerance for COF in complex electrolyte, resulting in significantly improved electrochemical performance. At 1 A g−1, it exhibits a high specific capacity of 161.2 mAh g−1 and an excellent cycle life of approximately 100 % coulombic efficiency after more than 3,000 cycles. This work fully demonstrates the operability of the design strategy to synthesize COF from small molecular organics by introducing reactive functional groups and its great potential in the role of cathode materials in RAIBs. The success meanwhile provides an inspiration for the development of COF-based organic battery system in large-scale energy storage.
Keywords: Rechargeable aluminium ion batteries; Covalent organic frameworks material; Triphenylamine; 40 Engineering; 4016 Materials Engineering; 7 Affordable and Clean Energy; Chemical Engineering; 4004 Chemical engineering; 4011 Environmental engineering; 4016 Materials engineering